STRATEGI KOMUNIKASI PETUGAS CTB PRA NPC PAYMENT COLLECTIONS DALAM MENAGIH PEMBAYARAN PELANGGAN INTERNET INDIHOME (STUDI PADA BAGIAN PETUGAS CTB DI PT. TELEKOMUNIKASI INDONESIA, TBK. WITEL SURABAYA) - Novianto, Ardian; Yuliyanti, Tri; Wibowo, Judhi Hari (representamen, 2016)
The participation of CTB officers not only provide information, but also expected to be able to handle all kinds of issues that could come at any time the customer location and able to provide the best solutions for customers in resolving problems indihome internet bill PT. Telekomunikasi Indonesia, Tbk. The types of problems that were varied. The problem is revealed here on the communication strategy officer CTB in collections Internet subscribers indihome PT. Telekomunikasi Indonesia, Tbk as customer facing cultural character, customers feel aggrieved because of the disruption of network and internet technical indihome. Researchers used the theory that interpersonal communication in communicating issues CTB officer charges made directly face to face with customers. The result of this research is the communication strategy used clerk CTB before the charge to the customer can work well and produce fade back thus creating communication between officers CTB with the customer. Keyword : interpersonal communications, the effect of a change in attitude.